Faktor – faktor yang mempengaruhi pendapatan pedagang di kawasan objek wisata Gunung Kerinci Kecamatan Gunung Tujuh di Kabupaten Kerinci - Muhammad Ilham; Syamsurijal Tan; Nurhayani Nurhayani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
This study aims to: 1) identify and analyze the social and economic characteristics of traders in the area of Gunung Kerinci Tourism Object, Gunung Tujuh District. 2) To know and analyze the income of traders in the area of Gunung Kerinci Tourism Object, Gunung Tujuh District and 3) To determine and analyze what factors influence the income of traders in the area of Gunung Kerinci Tourism Object, Gunung Tujuh District by using multiple linear regression analysis tools. Based on the results of multiple linear regressions it can be concluded that partially only the variable operating capital length of business and the number of dependents that have a significant effect on the income of traders in the area of Gunung Kerinci Tourism Object, Gunung Tujuh District. While the variables of location and level of education do not have a significant effect on the income of traders in the area of Gunung Kerinci Tourism Object, Gunung Tujuh District.